Importance of modern communication technologies in monitoring compliance of patients with chronic myeloid leukemia - Matić, Nikolina, medicinska sestra (Array, 2019)
Compliance is a term that applies to the patient’s ability to correctly follow advice and instructions regarding medications, diet, and activity. The nurse, as an important factor in the multidisciplinary team, has a special responsibility in monitoring the patient’s compliance. It is essential for patients with chronic malignancies, such as chronic myeloid leukemia, which is nowadays mostly treated successfully by continuous and regular monitoring and application of therapy. The aim of the present study was to determine whether the nurse’s communication with patients, which implies the use of information and communications technology, affects compliance. The study was conducted on a sample of 50 outpatients at the Department of Haematology of the University Hospital Centre Zagreb. The respondents used some form of modern communication for three weeks and were re-interviewed for compliance. The use of modern information technology enhances patient compliance. Those who were reminded significantly improved the regularity of their check-ups. After the intervention, the respondents considered reminders useful in encouraging them to take medicines more regularly and to attend check-ups.